Trophic Plasticity of Bombay Duck (Harpadon nehereus) in the South-Central East China Sea Based on Stable Isotope Evidence - Song, Pu-Qing; Zhang, Hu-Shun; Zheng, Xin-Qing; Li, Yuan-Yuan; Lin, Long-Shan; Li, Yuan (Frontiers in Marine Science, 2021)
High trophic plasticity is often invoked to explain the successful expansion of many aquatic species. Bombay duck (BD) outcompete other traditionally commercial fishes in the East China Sea (ECS) in recent years, displaying a continuous and sharp increase of catches, however, little is known whether the competition advantage of BD was related to its trophic plasticity. Using stable isotope analysis (SIA), we investigated the trophic ecology of BD in the south-central ECS in two periods. Significant differences in δ13C and δ15N values were found between sampling months and among body sizes. Modal (95% credibility limits) estimation showed that BD’s trophic position (TP) gradually increased from 3.56 (3.31-3.82) in G1 (120-150mm for body size) to 4.09 (3.69-4.50) in G5 (241-270mm) in November, and from 3.37 (2.92-3.88) in G2 (151-180mm) to 3.66 (3.07-4.23) in G4 (211-240mm) in April, respectively, suggesting obvious ontogenetic variation of δ15N and TP. More importantly, the TP of BD within the same body size showed wide amplitude, indicating BD possess high trophic plasticity, and can capture prey from low to high trophic levels. Further quantitative analysis based on the MixSIAR model showed that BD mainly fed on zooplankton and fish, but its feeding habit was characterized by the consumption of gradually reduced zooplankton and increased fish associated with increased body size. Interestingly, the fish’s contribution to BD showed obvious seasonal variation. It can be explained by varied food availability in ECS. Relatively low fish prey in April forced BD to adjust its diet, adding the ingestion of shrimps and cephalopods corresponding to temporal variations in food availability. The present study provides the evidence that high trophic plasticity exists in the feeding strategy of BD, which is reflected in the ability to adjust the feeding preference according to nutritional needs and food environmental changes; thus, it is competitively advantageous and may partly explain why BD is becoming the predominant species and displays an extensive distribution in the ECS.